2018
DOI: 10.1029/2017jb015223
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Geothermal Reservoir Processes at the Raft River Geothermal Field, Idaho, USA, Through Modeling InSAR‐Measured Surface Deformation

Abstract: Ground surface deformations detected with interferometric synthetic aperture radar provide valuable information for inferring subsurface reservoir processes that are difficult to observe directly. This study aims at building a reservoir model that honors the available geological, hydrological, and geomechanical data and also produces ground surface deformation consistent with interferometric synthetic aperture radar measurements at the Raft River Geothermal Field. In the thermo-hydro-mechanical coupled model d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
5
17
0
Order By: Relevance
“…The best-fitting permeability for the injection reservoir is 5.9 ± 1.5 × 10 −13 m 2 in the direction of slow diffusion, which is trending N70°E, and 8.3 ± 2 × 10 −13 m 2 in the direction of fast diffusion, which is trending N20°W. The N70°E permeability is within error from the value of 4.7 × 10 −13 m 2 used by Liu et al (2018), while the N20°W permeability indicates faster diffusion than predicted in their study. While we are unable to directly determine the specific physical mechanism behind our observed anisotropy, we hypothesize that it arises from pre-existing fractures, which are oriented ∼N-S (Liu et al, 2018;Nash & Moore, 2012).…”
Section: Resultsmentioning
confidence: 49%
“…The best-fitting permeability for the injection reservoir is 5.9 ± 1.5 × 10 −13 m 2 in the direction of slow diffusion, which is trending N70°E, and 8.3 ± 2 × 10 −13 m 2 in the direction of fast diffusion, which is trending N20°W. The N70°E permeability is within error from the value of 4.7 × 10 −13 m 2 used by Liu et al (2018), while the N20°W permeability indicates faster diffusion than predicted in their study. While we are unable to directly determine the specific physical mechanism behind our observed anisotropy, we hypothesize that it arises from pre-existing fractures, which are oriented ∼N-S (Liu et al, 2018;Nash & Moore, 2012).…”
Section: Resultsmentioning
confidence: 49%
“…The number of wells is relatively small and the geological setting is simple and well documented (e.g., Bradford et al, 2013;Nash and Moore, 2012). In addition, a prominent geodetic signal has been previously observed using Synthetic Aperture Radar Interferometry, InSAR (Liu et al, 2018;Ali et al, 2018). Such measurements can indeed provide important constraints on the spatio-temporal evolution of the pressure field and fluid flow in the sub-surface reservoirs (Ali et al, 2018, Hoffmann et al, 2001Chaussard et al, 2014).…”
Section: Accepted Articlementioning
confidence: 85%
“…These injecting wells extend to the basement (~1550m depth) but are open at depths greater than 500m. The majority of the reinjected cold water flows into a "thief zone" consisting of ~300m thick permeable layer at 500m depth (Liu et al, 2018;Ahmed et al, 1979;Spencer, 1979;Bradford et al, 2013).…”
Section: Accepted Articlementioning
confidence: 99%
“…The availability of radar systems with diverse wavelengths and cadences increases the applicability of InSAR to a wide variety of geophysical studies, including monitoring geothermal processes. In particular, differential InSAR (DInSAR) has been widely used to monitor surface deformation at many geothermal sites in the Western U.S. Several studies have used observed subsidence to develop subsurface reservoir models (e.g., [3][4][5]). In addition, data sets of multiple InSAR pairs have been used to determine temporal variations in subsidence at geothermal fields (e.g., [6,7]).…”
Section: Interferometric Synthetic Aperture Radarmentioning
confidence: 99%